Pengembangan Kelas Daring dengan Penerapan Hybrid Learning Menggunakan Chamilo pada Matakuliah Pendidikan Kewarganegaraan - Ary Purmadi; M. Samsul Hadi; Lu'luin Najwa (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2018)
The objectives of this study are 1) to develop products from LMS Chamilo that can be used in civic education courses that are suitable for use in learning based on alpha and beta tests. 2) Determine the effectiveness of product use in the citizenship course. The research method used in this research is research and development (R&D). The results of the feasibility of this product are based on the alpha test (alpha test) on the material expert of 3.25 which is included in the "good" category, while for the media expert it is 4.42 which is included in the "very good" category. In the beta test (beta test) of 3.93 which is included in the "good" category. From the results of the due diligence it can be stated that the product developed has met the elements suitable for use in the learning process. There was an increase in the achievement of student cognitive learning outcomes after using chamilo of 10.13. The pretest mean score was 60.13 and posttest 70.26. From the results of this study it can be concluded that learning using chamilo has been effective.